The effect of maximal aerobic speed training combined with small-sided games on performance parameters in soccer - Yüksel, Y.; Cerrah, A. O.; Tasçioglu, R.; Akdogan, E.; Gürol, B.; Yilmaz, I. (Kinesiology, 2023)
The purpose of this research was to compare the effects of maximal aerobic speed (MAS) training, small-sided games (SSG) training, and combined training (CT) on sprint, agility, lactate accumulation, repeated sprint, aerobic, and anaerobic endurance performances. Thirty under-16 male players participated in a 6-week randomized training study. Pre- and post-training all players completed a test battery involving body composition (body height and Dual Energy X-Ray Absorptiometry-DEXA), sprint tests (10 m, 20 m, and 30 m), Yo-Yo 1 test, Arrowhead agility test, blood lactate test, and Yo-Yo 2 test. A global positioning system (GPS) was used for monitoring. After the pre-tests, the players were randomly assigned to three groups as MAS, SSG, and CT. Mixed two-way ANOVA was used to compare the pre-test and post-test performance of the three groups. While the CT group had higher changes in body composition, repeated sprint, aerobic, and anaerobic endurance parameters compared to the MAS training group (p<.05), the SSG training group had similar changes as the CT group (p>.05). In conclusion, coaches and sports scientists are advised to choose CT for more efficient training, considering the differences between the MAS training and CT methods.